Clinical and vaginal microbiological characteristics of genital herpes in 27 females - Zhan ZHANG; Li ZHANG; Huihui BAI; Xiaonan ZONG; Linyuan FAN; Ting LI; Zhaohui LIU (Pifu-xingbing zhenliaoxue zazhi, 2024)
Objective To understand the clinical characteristics and microecological status of lower genital tract in females with genital herpes in gynecological clinic in order to standardize the treatment of genital herpes. Methods A total of 27 women diagnosed with genital herpes were enrolled from the gynecological clinic of Beijing Obstetrics and Gynecology Hospital, Capital Medical University. The clinical data and vaginal microecology of participants were analyzed. Results All patients presented with various degree of external genital itching, pain, burning pain, sting pain, etc. Gynecological examination showed typical external genital herpes and/or irregular small ulcers. One case presented with cervical herpes-like changes. Abnormal vaginal microecology was observed in 88.89% of the patients (24/27), including 8 cases of decreased function of flora, 2 cases of bacterial vaginosis, 6 cases of vulvovaginal candidiasis, 7 cases of abnormal flora, and 1 case of mixed infections. The pH of vaginal secretions was higher, evidenced by 22 cases (22/27, 81.48%) with pH >4.5. Conclusions The clinical manifestations of female genital herpes vary and are often accompanied by vaginal dysbiosis. In clinic, it is recommended to conduct vaginal microbiota examination and personalize targeted treatment for all women with suspected genital herpes.